The Effect Of The Form Of Parental Participation On Students Motivation To Learn Science In Bayang Elementary School Makassar City - Dian Amalia Malik; Widya Karmilasari Achmad; Nurfaizah AP (International Journal of Elementary School Teacher, 2021)
This study is a ex post facto study that aims to determine the significant effect of parental participation on the science learning motivation of students at SD Negeri Bayang Makassar City. The independent variable in this study is the form of parental participation, while the dependent variable is students' motivation to learn science. This study uses a quantitative approach. The population in this study were students of SD Negeri Bayang Makassar as many as 312 students. (1) determination of the sample of this study using simple random sampling technique as many as 172 students spread from grades I - VI SD. (2) data were collected using research instruments in the form of questionnaires and documentation (3) the data analysis technique used in hypothesis testing is statistical testing, including descriptive statistical analysis and inferential statistical analysis. The results of hypothesis testing show that significance value 0,03 then H0 is rejected and Ha is accepted. Based on the results of the study, it shows that there is a positive influence between parental participation on the science learning motivation of students at SD Negeri Bayang Makassar City